WAP (Wireless Application Protocol) Based New Student Admissions Information System at MTS. Nur Baharudin - Azhar, Azharudin; Firdaus, Uus; Susanti, Aisah Rini; Haq, M. Abu Ridho Abdul; Fachrani, Jihan; Syah, Dava Alhamda Putra; Zakaria, Muhammad Sultan Pasya (Universitas Mohammad Husni Thamrin, 2025)
In the digital era that continues to develop, information technology has become an integral component in various aspects of life, including the education sector. Globally, the application of technology-based systems in education has helped increase efficiency, transparency and accessibility. Developed countries such as Finland, Singapore and the United States have adopted online-based registration systems to provide inclusive and modern education services. Technological developments in the smartphone sector are increasingly advanced, marked by the competition between smartphone companies to create various kinds and types of smartphones with specifications that resemble computers in general. Which is supported by capable hardware and software. The development of the Android operating system is progressing rapidly every year. This development is one of the forerunners to the emergence of the Industrial Revolution 5.0 with the support of IoT (Internet of Thinks). Where humans use the Android system and internet network to meet their needs and solve work problems without having to move an inch. With the fairly advanced development of smartphones, supported by smartphone ownership owned by every element of society and an internet network that the public can now enjoy. It could be a solution used by the world of education to make learning easier and even make it easier for students to register online. By developing a WAP (Wireless Application Protocol) based system which is an innovative solution to facilitate the online registration process via mobile devices, especially in environments with limited internet infrastructure.